2001
DOI: 10.1108/02651330110389972
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between market orientation and innovation in the European and US insurance markets

Abstract: Despite the increasing research importance of market orientation in the marketing literature, few comparative studies between the European Union and the USA have been conducted. This limits the understanding of marketing orientation strategy in global markets. Investigates the influence of competitive environments on the uses of market orientation in insurance firms in the EU and the USA and the effects of market orientation on innovations. Using Lambin's conceptualization of market orientation, our results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(60 citation statements)
references
References 65 publications
5
51
0
2
Order By: Relevance
“…Market Orientation measures are based on the study by Lado, Maydeu-Olivares, and Rivera (1998) and by Lado, and Maydeu-Olivares (2001). Appendix 1 presents marketing practices measures.…”
Section: Methodsmentioning
confidence: 99%
“…Market Orientation measures are based on the study by Lado, Maydeu-Olivares, and Rivera (1998) and by Lado, and Maydeu-Olivares (2001). Appendix 1 presents marketing practices measures.…”
Section: Methodsmentioning
confidence: 99%
“…Hortinha et al (2011) observed a positive relationship between market orientation and business performance. Researchers such as: Kohli and Jaworski (1996;Slater and Narver, 1994;Lado and Maydeu-Olivares, 2001;Yoon and Lee, 2005;Lai et al, 2009;Mahmoud et al, 2010;Smirnova et al, 2011;Bahman and Mehdi, 2011;Mashahadia et al, 2016) have all observed a positive relationship between market orientation and business performance. According to Herhausen (2016) market orientation has an incremental positive effect on business performance.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…According to Lado & Maydeu-Olivares (2001), a model of market orientation should focus on innovation, which is defined as the implementation of ideas, products, or new processes, as a primary strategy to respond the market changes. This is according to Han et al (1998) suggest that market orientation is a primary determinant of innovation.…”
Section: Market Orientation and Business Performancementioning
confidence: 99%
“…Interest in the study of the concept of market orientation caused by empirical evidence shows that companies with higher market orientation tend to get higher business performance. Many researchers have found empirical evidence of the positive effect of a market orientation on business performance (Lado & Maydeu-Olivares, 2001). Narver and Slater (1990), provides an understanding of market orientation, suggesting that the market orientation mainly consists of three orientations of behavior that is customer orientation, competitor orientation, and inter-functional coordination.…”
mentioning
confidence: 99%